Acute and 28-Day Subchronic Oral Toxicity of an Ethanol Extract of Zingiber zerumbet (L.) Smith in Rodents. (27th March 2012) - Chang, Chia Ju; Tzeng, Thing-Fong; Liou, Shorong-Shii; Chang, Yuan-Shiun; Liu, I-Min
Abstract : The objective of this study was to evaluate the acute and subacute toxicity (28 days) of the ethanol extract of Z. zerumbet rhizomes (EEZZ) via the oral route in Wistar rats of both sexes. In the acute toxicity study, Wistar rats were administered a single dose of 15 g kg −1 of body weight by gavage, and were monitored for 14 days. EEZZ did not produce any toxic signs or deaths; the 50% lethal dose must be higher than 15 g kg −1 . In the subchronic toxicity study, EEZZ was administered by gavage at doses of 1000, 2000 and 3000 mg/kg daily for 4 weeks to Wistar rats. The subacute treatment with EEZZ did not alter either the body weight gain or the food and water consumption. The hematological and biochemical analysis did not show significant differences in any of the parameters examined in female or male groups. Necropsy and histopathological examination, did not reveal any remarkable and treatment related changes. A no-observed adverse-effect level for EEZZ is 3000 mg kg −1 for rats under the conditions of this study. Hence, consumption of EEZZ for various medicinal purposes is safe.